User involvement in the development of wireless applications in supply chains of the forestry industry. (1st December 2008) - Andersson, Per; Rosenqvist, Christopher; Valiente, Pablo
This study investigated how different users are involved in the development of new wireless applications for enterprises, here focusing on supply chain applications in the forestry industry. This article analyses the purpose, intensity and mode of user involvement when developing new wireless solutions by enterprise customers in close cooperation with solution suppliers. The article provides a theoretical overview of the research development of user involvement, with a focus on theories and concepts related to the customer involvement. An empirical case study forms the foundation for the analysis and discussion. Our investigation of the mode, intensity and purpose during the process revealed that user involvement can be described as a combination of commitment and participation components that there is an inverse relationship between the intensities of commitment and participation, and finally that user involvement can reduce uncertainties at the enabling, commissioning and impact levels.